Comparative study of peace negotiations - Yetim, Orhan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
This study aims to investigate the mechanisms that support the success of peace negotiations. Two main factors are the focus of this work, which are third-party intervention and payoffs of parties. When third-party interventions are combined with payoffs of parties in peace negotiations, cooperation and communication among parties have increased, which supports the success of peace negotiations. Due to certain similarities including ethnic roots of insurgent organizations, their way of organizing and electoral systems, the peace negotiation with IRA that Conservative Party initiated offers an important case that can be compared with Resolution Process in Turkey. Lack of third-party intervention and changes in payoffs motivating parties to defect from negotiations caused problems in disarmament, legal roadmap and incorporation of the opposition issues. Supported by electoral victory of Labor Party, third-party interventions through creating commissions, setting binding deadline and conducting meetings highly contributed the solution of these problems and the signing of Good Friday Agreement in 1998. On the other hand, Turkey had suffered from lack of third-party interventions with regards to disarmament, withdrawal, legal reforms and harsh nationalist critics. The impact of regime change in Turkey on Resolution Process is also addressed as a main reason for declining any third-party intervention in 2013 although AKP government demanded a coordinator from the U.S for ensuring the trans-national collaboration in PKK problem in 2009.
Keywords: Peace Negotiations.